2004
DOI: 10.4049/jimmunol.172.8.5024
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-Specific Antibodies Impair the Development of Gastritis, Facilitate Bacterial Colonization, and Counteract Resistance against Infection

Abstract: In recent years, Abs have been considered a correlate rather than an effector of resistance against Helicobacter pylori infection. However, it is still poorly understood to what extent Ab production correlates with gastric immunopathology. Here we report that Abs not only are dispensable for protection, but they are detrimental to elimination of the bacteria and appear to impair gastric inflammatory responses. We found that the initial colonization with H. pylori bacteria was normal in the B cell-deficient (μM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
91
2
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 78 publications
(100 reference statements)
6
91
2
2
Order By: Relevance
“…Studies have suggested that locally produced antibodies, particularly IgA [13,14], might block H. pylori infection by preventing colonization and adhesion and allowing killing by neutrophils or monocytes through bacterial opsonisation [15,16]. Helicobacter-specific IgA monoclonal antibodies administered directly into the gastric lumen conferred protection against H. felis infection [11,17] and neutralized the toxic products of Helicobactor pylori [18]. The results of present study are in accordance with favourable role indicated in the above mentioned studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies have suggested that locally produced antibodies, particularly IgA [13,14], might block H. pylori infection by preventing colonization and adhesion and allowing killing by neutrophils or monocytes through bacterial opsonisation [15,16]. Helicobacter-specific IgA monoclonal antibodies administered directly into the gastric lumen conferred protection against H. felis infection [11,17] and neutralized the toxic products of Helicobactor pylori [18]. The results of present study are in accordance with favourable role indicated in the above mentioned studies.…”
Section: Discussionsupporting
confidence: 89%
“…However, even though H. pylori infection stimulates strong local and systemic specific IgA and IgG antibody production, it is still controversial as to what influence antibodies may have on the bacterial colonization [7][8][9]. While earlier reports claimed eradication as well as protection from the infection by H. felis by active oral and passive IgA immunization [8,10], another study claims that antibodies were not only dispensable for protection, but also impaired elimination of bacteria and the development of gastric inflammation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Th2 cells do not appear to be needed for protection, but they may contribute to the severity of postimmunization gastritis, as suggested by observations made in IL-4-deficient mice (18,20). Moreover, Th2 cells increase in number in well-protected mice over time after immunization, perhaps indicating a role in long term protection (6,11). Thus, both Th1 and Th2 cells could be involved in the development of immune protection against H. pylori (11, 21).…”
Section: Vaccine-induced Immunity Against Helicobacter Pylorimentioning
confidence: 82%
“…Thus, both Th1 and Th2 cells could be involved in the development of immune protection against H. pylori (11, 21). These observations, in addition to the dominance of eosinophilic cells in well-protected gastric mucosa, suggest a common regulatory link between Th1-and Th2-dependent functions, promoting resistance to H. pylori infection (6,12). One factor that could fulfill such a role is IL-18, which is known to affect Th1 development/IFN-␥ production as well as influence Th2-controled functions (22,23).…”
Section: Vaccine-induced Immunity Against Helicobacter Pylorimentioning
confidence: 99%
“…However, the key role of Th1 cells in inducing the secretion of IgG by activated plasma cells or the activation of macrophage killing appear to be dispensable for protection [37][38][39]. Immunity might be facilitated by as yet unknown effector mechanisms and it is important to explore novel cell types or molecules in immunity to this end.…”
Section: Discussionmentioning
confidence: 99%